(untitled) (Global Journal of Human-Social Science, 2018)
The teacher plays a vital role in students’ learning. I think main motive of the education should be to build the overall character and to bring the all-round development of the students. A sound education system is the prerequisite for the development of any nation. This is a well-known fact that our education system still relies on traditional methods and there is a need to combine the traditional teaching with modern teaching aids for a better and advanced education system. The main objective of this article is to focus on the analysis of teaching techniques, ranging from the use of the blackboard and chalk in old traditional classes, using slides and overhead projectors in the eighties and use of presentation software in the nineties, to the video, electronic board and network resources nowadays. Whether traditional or modern methods of teaching are adopted, the teacher has a desired outcome in mind. The main difference is in ensuring that learning is permanent and the student is able to draw connections between what is taught with the real world. The teacher’s importance is not undermined whether one uses the conventional method of teaching or introduces technology in the classroom. There is no point in discussing that which teaching method is better than the other? Instead we should concentrate on providing the best education system to the students as it’s the students who will run the nation in future. I think we can develop a better education system only if we will be able to combine both the traditional and modern teaching methods.